Penguatan Kompetensi Pembuatan Bahan Ajar Bahasa Indonesia bagi Penutur Asing Berbasis Budaya dan Tradisi Jawa bagi Dosen Fatoni University Thailand (FTU) - Kundharu Saddhono; Muhammad Rohmadi; Ani Rakhmawati; Islahuddin Islahuddin; Aldi Dwi Saputra; Maulana Danar Maaliki H (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This training aims to improve the competence of Fatoni University Thailand (FTU) lecturers in developing Indonesian language teaching materials for foreign speakers with a focus on Javanese culture and traditions. The dedication team consisted of 3 lecturers from Sebelas Maret University, one lecturer from Fatoni University, and three students from Sebelas Maret University. The training was held at Fatoni University, Thailand on 31 May – 7 June 2023. The training participants were Fatoni University lecturers who taught Indonesian for Foreign Speakers (BIPA) at the Malay Language Faculty. The training is carried out in 3 major stages, namely: the preparation stage, the implementation stage, and the evaluation stage. During the training, participants are provided with a comprehensive understanding of Javanese culture and traditions, including values, traditional ceremonies, special foods, traditional clothing, customs, and relevant cultural symbols. The trainees are actively involved in group work sessions, where they design Indonesian language teaching materials with Javanese cultural and traditional themes. They use their knowledge and creativity to plan engaging lessons and focus on cultural content. The evaluation results show that this training succeeded in increasing the competence of lecturers in developing teaching materials based on Javanese culture and traditions. This training provides a solid foundation for Fatoni University to continue to develop an Indonesian Language learning program for Foreign Speakers (BIPA) based on culture and tradition. Fatoni University lecturers who have participated in this training are expected to be able to apply teaching materials based on Javanese culture and traditions in learning, provide a more authentic and interesting learning experience for Indonesian Language students for Foreign Speakers (BIPA).